Influencing factors of psychological stress under the mixed teaching mode based on SPOC+PBL - Shen, Guorong; An, Yide (Frontiers in Psychology, 2022)
In the teaching process, teachers and students are under different psychological pressures. Especially under the influence of the epidemic, many teaching modes have been transformed from traditional classroom teaching to online teaching. Under the new teaching mode, especially the promotion and application of the blended teaching mode, classroom teaching is facing new challenges, and both students and teachers are facing new psychological pressures. If the psychological pressure is not resolved, the classroom effect will be even worse. Therefore, the purpose of this paper is to analyze the source of the influencing factors of psychological stress under the new teaching mode, which is a rarely involved direction in the teaching field, and is of great significance for the promotion and application of the new teaching mode. Aiming at the blended teaching model, this paper focuses on the SPOC+PBL blended teaching model, designs a new teaching model of “English-Chinese translation and interpretation”, and studies the sources of pressure under the new model. Aiming at the influencing factors of psychological pressure, a psychological pressure model is established to explore the influence of six factors on psychological pressure. The experimental results of this paper show that the factor loadings of all variables are greater than 0.5, indicating that “self-esteem strength”, “self-efficacy”, “help-seeking experience”, “psychological counseling cognitive bias”, “counseling object positioning bias” and “psychological counseling” “Resources” and “availability” have a greater impact on psychological stress.